The Influence of Communication and Monetary Rewards as Motivation Strategies on Students’ Academic Performance - Mbiti, Marysella Mumbua; Mulwa, David M.; Maithya, Redempta (International Journal of Education and Research, 2015)
The purpose of this study was to establish the influence of communication and monetary rewards on students; academic performance. The study was guided by two objectives that focused on communication and monetary rewards teachers’ as strategies of motivating teachers and their influence on students’ academic performance. The study was conducted in all public secondary schools in Kathiani district. The target population included all the 30 Principals, 150 Heads of Department and 320 teachers working in the district. The District Education Officer (DEO) and the District Quality Assurance and Standards Officer (DQASO) were also targeted in the study. Using simple random sampling method, a sample of 17 principals, 34 Heads of Departments and 68 teachers from the public secondary schools in the sub county were selected. The study used descriptive survey research design where questionnaires and an interview schedule were used as the main tools for data collection. Validity was assured through consultation with lecturers while a test-retest method was used to test for reliability of the instruments. Data analysis was done using descriptive and inferential statistics. All the null hypotheses were tested at .05 level of significance. The findings revealed that teachers were dissatisfied with the manner that principals handled matters of communication and monetary rewards. It was further revealed that there was statistically a positive and significant influence of communication and monetary reward strategies of teacher motivation on students’ academic performance (p<.05). Using the coefficient of determination (r2), the study found out that monetary reward and communication could each explain respectively about 66% and 64% of the total variance on students’ performance.
Keywords: Communication; Monetary Rewards; Motivation